1989
DOI: 10.1111/j.1432-1033.1989.tb14828.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of light on the biosynthesis of leaf‐specific thionins in barley, Hordeum vulgare

Abstract: In barley seedlings grown in the dark large amounts of thionin‐specific mRNAs are present, the concentration of which rapidly declines once the seedling is exposed to light. This rapid light effect is mediated by a complex interaction of possibly two photoreceptors, phytochrome and a blue‐light‐absorbing photoreceptor. Parallel to the decline in mRNA content, the de novo synthesis of leaf‐specific thionins ceases rapidly upon illumination of etiolated seedlings. However, thionins which have accumulated before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Although it has been reported that the basal levels of other defense-related genes are modulated by light (Reimann-Philipp et al, 1989), it is unexpected that light appears to be a requirement for the induction of a defense gene by bacterial infiltration. Similarly, other genes involved in plant adaptive responses, like a desiccation-inducible gene of Craterostigma plantagineum, k ave been shown to be regulated by light (Bartels et al, 1932).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that the basal levels of other defense-related genes are modulated by light (Reimann-Philipp et al, 1989), it is unexpected that light appears to be a requirement for the induction of a defense gene by bacterial infiltration. Similarly, other genes involved in plant adaptive responses, like a desiccation-inducible gene of Craterostigma plantagineum, k ave been shown to be regulated by light (Bartels et al, 1932).…”
Section: Discussionmentioning
confidence: 99%
“…Steady state messenger levéis seemed to be higher in the lower 1/3 of the leaf (younger cells) than in the upper 2/3 (older cells) and to decline sharply upon illumination (Gausing, 1987). The effect of light has been further investigated by Reimann-Philipp et al (1989a), who have postulated the mediation of two photoreceptors, phytochrome and a blue-light-absorbing photoreceptor. Synthesis of thionins concomitantly ceased upon illumination, but the previously accumulated thionin was rather stable (Reiman-Philipp et al, 1989a).…”
Section: Gene Expressionmentioning
confidence: 99%
“…* Corresponding author; e-mail bohlmann8ipw.agrl.ethz.ch; fax 41-1-632-1081. 81 3 concentrations of thionins (Reimann-Philipp et al, 1989a). Thionins that were isolated from leaves or the endosperm of barley were both toxic to plant pathogenic fungi and bacteria in vitro (Bohlmann et al, 1988;Florack et al, 1993;Molina et al, 1993;Terras et al, 1993).…”
mentioning
confidence: 99%